2021
DOI: 10.25181/jppt.v21i3.2139
|View full text |Cite
|
Sign up to set email alerts
|

JALUR INFEKSI Beauveria bassiana DAN Metarhizium anisopliae SEBAGAI PENGENDALI HAYATI COLEOPTERA:Oryctes rhinoceros L.

Abstract: Studi ko-evolusi terbaru serangga-patogen memperlihatkan bahwa cendawan entomopatogen memiliki potensi toksisitas oral yang lebih besar dalam virulensi pada infeksi mulut serangga hama. Oleh karena itu perlu dikaji invensi jalur infeksi B. bassiana dan M. anisopliae melalui alat mulut pada larva hama kumbang badak O. rhinoceros. Tujuan dari penelitian ini adalah menganalisis jalur infeksi B. bassiana dan M. anisopliae pada larva O. rhinoceros melalui metode pemaparan cendawan entompotagen, Penelitian dilaksana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…Different results regarding B. bassiana infection with a lower average death rate for O. rhinoceros larvae ranging from 20-55% with a longer death time on day 6 after infection. The results of microscopic identification of dead larvae showed that there were B. bassiana hyphae and conidia which strengthened the evidence of successful B. bassiana infection [11].…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Different results regarding B. bassiana infection with a lower average death rate for O. rhinoceros larvae ranging from 20-55% with a longer death time on day 6 after infection. The results of microscopic identification of dead larvae showed that there were B. bassiana hyphae and conidia which strengthened the evidence of successful B. bassiana infection [11].…”
Section: Introductionmentioning
confidence: 57%
“…Exposure to test insects using the immersion method for 2 minutes. Then there is an incubation period for maintenance and observation of the test larvae with periodic feeding until one of the replicates reaches 100% mortality [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It takes around 7 days for M. anisopliae to develop in the host body until the host passes away [18]. The duration of the M. anisopliae fungus' incubation period, according to [19], is between 5 to 10 days.…”
Section: The Initial Time Of Deathmentioning
confidence: 99%